Energy Efficiency Policies and Industrial Growth: Unlocking West Africa’s Production Potential - Ogunsola, Akindele John; Zwane, Talent Thebe (International Journal of Energy Economics and Policy, 2025)
The paper objective is crucial because the study analyzes how energy efficiency policies affect industrial growth in 16 West African countries from 2000 to 2023, therefore addressing the energy challenges and low industrial performance in the region for sustainable growth. The limited research with regard to the interplay of energy efficiency and industrial development in the context of West Africa motivated this study and integrates the endogenous growth theory, focusing on technological innovation, human capital, and resource efficiency. In particular, this study applies several high-tech econometric methods, namely the stochastic frontier and random effects models, to examine the effect of energy intensity, carbon emission intensity, renewable energy efficiency, and energy infrastructure on industrial, manufacturing, and productivity growth. The inefficiency in energy intensity and infrastructure dampens industrial growth. Also, governance quality and urbanization have a positive impact on productivity. The interaction between governance quality and energy policies amplifies productivity but worsens manufacturing growth. Carbon emission efficiency promotes manufacturing but detracts from productivity. This study, therefore, stresses the need for policy interventions that focus on governance improvement, energy infrastructure development, and renewable energy utilization to stimulate industrial growth in West Africa.